On the degree of approximation of the Hermite and Hermite-Fejer interpolation - J. Prasad (International Journal of Mathematics and Mathematical Sciences)
Here we find the order of convergence of the Hermite and Hermite-Fejér interpolation polynomials constructed on the zeros of (1−x2)Pn(x) where Pn(x) is the Legendre polynomial of degree n with normalization Pn(1)=1.